Growth, Production and Seed Quality of Brachiaria brizantha cv. Mg 5 Under Different Planting Space - Nafiatul Umami; Asrie Hardianing Indra Kusuma; Cuk Tri Noviandi (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The research aimed to investigate the effect of different planting space on the seed production of Brachiaria brizantha cv. MG 5.This study used three dimensions of spacing: 75 x 75 cm, 100 x 100 cm, and 150 x 150 cm. The seed was germinated before planted on the 3 x 3 m plot with three replications. Fertilization was performed twice at the age of 30 and 90 days with NPK fertilizer 400 kg ha-1 and given the same amount of water. The variables observed were the plants’ height, length, number of tiller, inflorescence, raceme, spikelet, the seed purity, the seed production (kg ha-1), and viability. The data obtained were analyzed statistically by using the Completely Randomized Design (CRD), and if any difference existed, it was continued with Duncan's new multiple range test. The results showed that the different planting space was significant (P<0.05) to the seed production of Brachiaria brizantha cv. MG5., which was the seed production at 75 x 75 cm spacing was 206.43 kg ha-1, 100 x 100 cm was 354.43 kg ha-1, and 150 x 150 cm was 128.87 kg ha-1. The highest seed production was resulted in planting space of 100 x 100 cm that was 354.43 kg ha-1.